Quality of patient safety indicators in intensive care units: Protocol for a systematic review - Isac Davidson Santiago Fernandes Pimenta; Ádala Nayana de Sousa Mata; Gidyenne Christine Bandeira Silva de Medeiros; Daniel Guillén-Martínez; Manuel Pardo Rios; Grasiela Piuvezam (PLoS ONE, 2026)
Patient safety is an important issue in intensive care units. Patient safety indicators are often incorporated without undergoing the proper process of development and validation, which leads to problems with construct validity, measurement reliability, feasibility, and comparability across institutions and countries. This study reports a protocol for a systematic review that aims to identify and assess the validity of patient safety indicators used in the intensive care unit context. This protocol was previously registered in PROSPERO (CRD42024617125). We will search for original studies in the following databases: PubMed (Medline), Scopus, EMBASE (Elsevier), CINHAL (EBSCO), Web of Science, Cochrane Database and Google Scholar for grey literature. We will include methodological or observational studies that report the construction and/or validation of patient safety indicators. Two reviewers will independently screen and assess the studies, and disagreements will be resolved by a third reviewer. We will assess the quality of the studies using the COnsensus-based Standards for the selection of health status Measurement INstruments (COSMIN) checklist. To assess indicator validity, we will use the Appraisal of Indicators through Research and Evaluation (AIRE) instrument. We will classify the indicators according to Donabedian attributes of structure, process and outcomes, as well as the contexts of intensive care, such as pediatric, neonatal or cardiac units, for example. We will also perform descriptive analysis of each category assessed. We expect that our review will contribute to providing a valid set of indicators and help to identify gaps regarding patient safety dimensions that need to be assessed by new indicators.